2023
DOI: 10.1097/j.jcrs.0000000000001106
|View full text |Cite
|
Sign up to set email alerts
|

Standard vs total keratometry for intraocular lens power calculation in cataract surgery combined with DMEK

Abstract: To compare the prediction accuracy of standard keratometry (K) and total keratometry (TK) for intraocular lens (IOL) power calculation in eyes undergoing combined cataract surgery and Descemet membrane endothelial keratoplasty (triple DMEK).Setting: Tertiary care academic referral center.Design: Retrospective case series.Methods: Review of 83 eyes (63 patients) that underwent triple DMEK between 2019 and 2021. Biometry measurements were obtained using a swept-source optical biometer (IOLMaster 700). 63 eyes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…It had been published that using adjusted conventional keratometry based on the postoperative posterior to preoperative anterior corneal curvature radii (PPPA) ratio and a ctious refractive index (FRI), reduces hyperopic DIRS, thus providing more accurate refractive outcomes than using standard keratometry; and it is non less effective than selecting a myopic target between − 0.50 and − 1.00 D. 28 On the other hand, more recently, a study in eyes undergoing triple-DMEK was published in which the authors concluded that the prediction accuracy of standard keratometry was superior to TK, being the SRK/T and multivariate formulae with the IOLup1D adjustment the most accurate. 27 These ndings are consistent with the results of our study. Even though the SRK/T formula with optimized constant was the one which showed a better performance (Table 4 and Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It had been published that using adjusted conventional keratometry based on the postoperative posterior to preoperative anterior corneal curvature radii (PPPA) ratio and a ctious refractive index (FRI), reduces hyperopic DIRS, thus providing more accurate refractive outcomes than using standard keratometry; and it is non less effective than selecting a myopic target between − 0.50 and − 1.00 D. 28 On the other hand, more recently, a study in eyes undergoing triple-DMEK was published in which the authors concluded that the prediction accuracy of standard keratometry was superior to TK, being the SRK/T and multivariate formulae with the IOLup1D adjustment the most accurate. 27 These ndings are consistent with the results of our study. Even though the SRK/T formula with optimized constant was the one which showed a better performance (Table 4 and Fig.…”
Section: Discussionsupporting
confidence: 93%
“…8, 24,26 As described in the literature and supported by our ndings, obtaining accurate keratometric measurements in patients with FECD may be more challenging. 27 Nevertheless, persevering in obtaining measurements labelled as "Successful" by the biometer would be advantageous, as this approach would lead to a lower dispersion of data and enhance the predictability of refractive outcomes. We have shown a reduction in centroid ellipsoid radii of the DAVDs when analyzing the change in astigmatism in this subgroup (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical retrospective comparative study, Danjo et when TK was used 46 . Similarly, studies have demonstrated that TK is superior to K in cases with complex corneal conditions such as combined corneal endothelial diseases and keratoconus 47,48 . Therefore, in designing this study, we used BUII with K preoperatively and compared TK and K postoperatively.…”
Section: Discussionmentioning
confidence: 97%
“…LT and WTW can be added optionally. (5) The PEARL-DGS formula (www.iolsolver.com) uses obligatory parameters AL, K, and ACD. Optional parameters are LT, CCT, and WTW.…”
Section: Iol Power Calculationmentioning
confidence: 99%
“…Improvements in commonly used intraocular lens (IOL) power calculation schemes led to new-generation formulas that aim to reduce trend errors and achieve better refractive outcomes and higher patient satisfaction, especially in cases that are more demanding. 2–11 Among these new formulas, the Barrett Universal II (BU2), Emmetropia Verifying Optical (EVO) 2.0, Hill–Radial Basis Function (RBF) 3.0, Kane, Castrop, and PEARL-DGS formulas are among the more commonly used IOL formulas in studies and clinical practice that offer free online calculation websites (accessible via https://iolcalculator.escrs.org/ and/or https://iolcon.org/lpcm.php).…”
mentioning
confidence: 99%